2018
DOI: 10.1109/rita.2018.2879388
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Innovative Approaches in the Class Using Conceptual Maps and Considering the Learning Styles of Students

Abstract: This paper presents innovations to stimulate the autonomy of engineering students by using different active methodologies. The strategies designed to address this problem are based on analyzing students' learning styles and incorporating specific tools into teaching practice, such as "M-eRoDes", which supports the automatic evaluation and feedback of concept maps created by them. Among the main findings, the students' assessment of the activity "making concept maps" stands out as useful but not easy. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…Moreover, Pablico et al (2017) suggested differentiated instruction strategies for science education in high schools that cater to auditory, visual, and kinesthetic learners. Coma-Roselló et al (2018) presents innovations aimed at stimulating the autonomy of engineering students by various active methods. Strategies designed to address this issue are based on an analysis of students' learning styles and integrate specific tools in the teaching practice, which aid in assessment and automatically respond to student-generated concept maps.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Pablico et al (2017) suggested differentiated instruction strategies for science education in high schools that cater to auditory, visual, and kinesthetic learners. Coma-Roselló et al (2018) presents innovations aimed at stimulating the autonomy of engineering students by various active methods. Strategies designed to address this issue are based on an analysis of students' learning styles and integrate specific tools in the teaching practice, which aid in assessment and automatically respond to student-generated concept maps.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los objetivos, por ejemplo, se van precisando a medida que se definan los contenidos. Para la secuenciación de contenidos pueden emplearse herramientas como esquemas, tramas de contenido que permitan encontrar la interrelación de estos, y mapas conceptuales (Cañas, 2016;Coma et al, 2018). Las actividades incluyen la forma como se enseña y se aprende: no es la actividad concreta la que posibilita aprender, sino el proceso completo diseñado, es decir, el conjunto de actividades organizadas y secuenciadas que posibilitan la interacciones entre los profesores, los estudiantes y el material didáctico.…”
Section: Unidades Didácticasunclassified